Brains, complex systems and therapeutic opportunities in epilepsy. (August 2021) - Scott, Rod C.
Highlights: The concept of epilepsy as a network disease is gaining traction, particularly at the level of whole brain. This concept falls within a complex adaptive system framework that is explored in this paper. Networks at gene, protein and microcircuit levels are underexplored in epilepsy. Understanding such networks has enormous potential for extending pathophysiological, mechanistic and therapeutic hypotheses. Abstract: The treatment of epilepsy remains extremely challenging for the thirty percent of people that do not become seizure free. This is despite the introduction of multiple new drugs over that last several decades, highlighting the need for new approaches to identifying novel therapeutic strategies. Conceptualizing the brain as a complex adaptive system and applying the tools that are used in addressing such systems provides an opportunity for expanding the space in which to search for new therapies. Epilepsy has long been considered a network disease at the level of whole brain connectivity, but the application of the concepts to gene and protein expression networks as well as to the dynamic behaviors of microcircuits has been underexplored. These levels of the brain complex adaptive system will be reviewed and a case made for the epilepsy community to embrace these concepts in order to reap to enormous potential rewards.